"It's a beer!": Brain functional hyperconnectivity during processing of alcohol‐related images in young binge drinkers. (7th February 2022) - Almeida‐Antunes, Natália; Antón‐Toro, Luis; Crego, Alberto; Rodrigues, Rui; Sampaio, Adriana; López‐Caneda, Eduardo
Abstract: Alcohol attentional bias has been pointed as a major marker of alcohol misuse. Recent evidence has revealed that brain functional connectivity (FC) may be a valuable index of the brain networks' integrity in young binge drinkers (BDs). However, there is no study to date examining the FC networks linked to the processing of alcohol‐related images in this population. The present study aimed to explore the FC signatures underlying alcohol attention bias in young BDs. Thus, electroencephalographic (EEG) activity was recorded in 54 college students (55.5% females; 27 non/low‐drinkers and 27 BDs) while performing a visual alcohol cue‐reactivity task. We evaluated whole‐brain FC profiles during the processing of alcoholic and non‐alcoholic cues, as well as their potential relationship with craving and severity of alcohol use. Results showed that, at the behavioural level, BDs rated alcohol‐related images as more pleasant/attractive than non/low‐drinkers. Furthermore, at the electrophysiological level, BDs exhibited increased beta‐band FC—particularly in the fronto‐parieto‐occipital network—when processing alcoholic cues. Conversely, they displayed reduced theta‐band FC relatively to non/low‐drinkers for non‐alcoholic images. These hyper‐/hypo‐connectivity patterns were associated with higher alcohol craving levels. Findings are congruent with previous neurofunctional studies reporting an attentional bias towards alcohol‐related information in BDs. These results may have important clinical implications as this neural reactivity to alcoholic cues may contribute to the maintenance and/or escalation of the drinking pattern. Finally, the present study constitutes the first evidence showing that FC networks may be a sensitive indicator to alcohol attentional bias in BDs. Abstract : The present study explored the functional connectivity (FC) signatures underlying alcohol attention bias in young binge drinkers (BDs). BDs exhibited beta hyperconnectivity towards alcoholic cues in comparison with non/low‐drinkers. Conversely, BDs showed reduced theta FC for non‐alcoholic cues. These abnormal FC patterns in BDs were mainly observed in fronto‐parieto‐occipital networks and were associated with harmful alcohol use and craving for alcohol. Overall, our findings are congruent with previous neurofunctional studies reporting an attentional bias towards alcohol‐related information in BDs.